Development of a Vibration Attenuation Track at Low Frequencies for Urban Rail Transit. (27th July 2017) - Zhu, Shengyang; Wang, Jianwei; Cai, Chengbiao; Wang, Kaiyun; Zhai, Wanming; Yang, Jizhong; Yan, Hua
Abstract: Railway‐induced vibrations at low frequencies have become an important environmental issue with the rapid development of urban rail transit. In this study, a new vibration attenuation track (VAT) capable of passively mitigating vibrations at low frequencies is developed based on an integrated theoretical and experimental study. The full‐scale VAT is built which incorporates a floating slab track (FST) and the attached dynamic vibration absorbers (DVAs) with key parameters determined by the fixed‐point theory and modal analysis technique. The vibration attenuation performance of the VAT is investigated under train dynamic loads by establishing a three‐dimensional coupled dynamic model of a metro vehicle‐VAT‐subgrade system, and is further elucidated and validated by carrying out full‐scale dynamic tests under different harmonic loadings. Computational and experimental results both show that vibrations of the track are effectively absorbed by the attached DVAs leading to a significant reduction of the subgrade vibrations at the low frequency of 9–16 Hz.